2019
DOI: 10.1088/1755-1315/393/1/012028
|View full text |Cite
|
Sign up to set email alerts
|

Bio agent added organomineral nitrogen fertilizer for heavy metal contaminated paddy field treatment

Abstract: Industrial waste in paddy field leads to accumulation of heavy metals in the soils. The availability of heavy metal on the soil can affect soil quality and plant growth. The objectives of this research were to obtain the best dosage of bio agent-added organomineral nitrogen fertilizer (ONF+BA) for the improvement of soil quality and paddy rice grown in industrial-waste contaminated soil. Randomized block design were applied with six single treatments: 150 kg ONF+BA (A), 200 kg ONF+BA (B), 250 kg ONF+BA (C), 30… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…Several studies have shown that the increased application of chemical fertilizers and pesticides contributes to an increase of heavy metals in potato farmland, including Pb, Cd, Cr, and As [8,43]. Furthermore, manure, husk ash, and straw compost as organic fertilizer also contribute to the Pb, Cd, and As contamination [44,45]. It is because the main ingredient of the previous fertilizer has also been contaminated with heavy metals both from the environment and during the cultivation process.…”
Section: Resultsmentioning
confidence: 99%
“…Several studies have shown that the increased application of chemical fertilizers and pesticides contributes to an increase of heavy metals in potato farmland, including Pb, Cd, Cr, and As [8,43]. Furthermore, manure, husk ash, and straw compost as organic fertilizer also contribute to the Pb, Cd, and As contamination [44,45]. It is because the main ingredient of the previous fertilizer has also been contaminated with heavy metals both from the environment and during the cultivation process.…”
Section: Resultsmentioning
confidence: 99%
“…Bio-organomineral fertilizer is a modification of Bio-organomineral N fertilizer with added biological agents, consisting of urea, palm bunch charcoal, zeolite, and compost with biological agents Pseudomonas cepacia and Bacillus subtilis (Sudirja et al, 2019). Bio-organomineral fertilizer application increases pH compared to the control (Widodo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%